Synthesis of 4,4'-Arylmethylene-bis(3-methyl-5-pyrazolones) using Diammonium Hydrogen Phosphate as an Efficient and Versatile Catalyst in Aqueous Media - Yang, Chunguang; Pang, Lijuan; Wang, Airong (Asian Journal of Chemistry, 2010)
A simple and efficient synthesis of 4,4'-arylmethylene-bis(3-methyl-5- pyrazolones) has been accomplished by the tandem Knoevenagel-Michael reaction of arylaldehydes with two equivalents of 5-methyl-2-phenyl-2,4-dihydro-3H- pyrazol-3-one using diammonium hydrogen phosphate as an efficient and versatile catalyst in aqueous media.